2004
DOI: 10.1007/s00213-004-2029-x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying target regions for vigilance improvement under hormone replacement therapy in postmenopausal syndrome patients by means of electroencephalographic tomography (LORETA)

Abstract: Electroencephalographic tomography (LORETA) identified the right-hemispheric vigilance system as the target region of Climodien.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…Consistent with findings from functional neuroimaging (Buchsbaum et al, 1990;Lewin et al, 1996;Paus et al, 1997;Sturm et al, 2004) and neurophysiological studies (Bearden, Cassisi, & White, 2004;Saletu et al, 2005), the findings from the present investigation further implicate the right cerebral hemisphere in the sustained attention processes. The results of this study also extend the findings of previous research by providing researchers with a non-invasive methodology by which an individual's level of cortical arousal could be used to reliably predict his or her behavioral performance.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with findings from functional neuroimaging (Buchsbaum et al, 1990;Lewin et al, 1996;Paus et al, 1997;Sturm et al, 2004) and neurophysiological studies (Bearden, Cassisi, & White, 2004;Saletu et al, 2005), the findings from the present investigation further implicate the right cerebral hemisphere in the sustained attention processes. The results of this study also extend the findings of previous research by providing researchers with a non-invasive methodology by which an individual's level of cortical arousal could be used to reliably predict his or her behavioral performance.…”
Section: Discussionsupporting
confidence: 91%
“…It has been shown that young women express relatively greater resting right frontal activity during the periovulatory phase compared to the menstrual phase 26 . An electroencephalographic study has also shown that the right hemisphere vigilance system can be enhanced by hormonal therapy in women with postmenopausal syndrome 27 . Estrogenic effects were reported to occur in the limbic-amygdala-hippocampal structures 5 , which can modulate higher perseverance for positive reward during the periovulatory phase 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering that MtFs identify with women, this is in line with evidence for estradiol enhancing right hemispheric functioning in women (Bayer & Hausmann, 2009; Hausmann, Becker, Gather, & Gunturkun, 2002; Weis et al., 2008) in regions involved in the fronto‐parietal network (Saletu et al., 2005). Even low doses of estradiol facilitate the functioning of brain regions involved in visual perception and attentional processes (Stevens, Clark, & Prestwood, 2005).…”
Section: Discussionmentioning
confidence: 99%